Diplomasi Publik Indonesia terhadap Sustainable Tourism Kompleks Candi Borobudur dan Prambanan - Suri, Adinda Dilah; Sidik, Hasan (Jurnal Hubungan Internasional, 2021)
This paper aimed to provide an overview of Indonesia's public diplomacy through the World Heritage Twin Programme on developing sustainable tourism and preserving the Borobudur and Prambanan Temple Compounds. Every World Heritage Sites in the world should apply the concept of sustainable tourism. We should maintain it, so its identity and value do not disappear. From the given background, this paper focuses on how Indonesia's public diplomacy could help develop sustainable tourism and preserve the Borobudur and Prambanan Temple Compounds. The author uses the qualitative research method to examine the issue with primary and secondary data sources from interviews with the expert and study of literature. The author's analysis shows some aspects, both from sustainable tourism and preservation, that the manager does not fulfill yet. However, as one of the forms of Indonesia's public diplomacy, World Heritage Twin Programme can help achieve those aspects and help develop sustainable tourism and preservation of Borobudur and Prambanan Temple Compounds.